Release of phospholipid fatty acid from human erythrocytes - Shohet, Stephen B. (1970)
To study the catabolism of erythrocyte phospholipids, human erythrocytes were labeled with radioactive fatty acid (FA). Labeling was performed by the two separate routes which together are thought to be responsible for the majority of phosphatide renewal in the red cell: (a) passive equilibration of erythrocytes with preformed acid-labeled red cell phosphatidylcholine (PC) and (b) active, “acylase”-dependent, incorporation of free fatty acid in the presence of ATP coenzyme A and magnesium. (As measured here “acylase” = the over-all effect of fatty acid thioesterification and the action of acyl-CoA: acylglycerophosphoryl acyltransferase.) The labeled cells were then reincubated in serum and the loss of radioactivity from cells into serum was examined. The phosphatide fatty acid introduced by these two routes was incorporated into two distinct cellular phosphatide pools with little mixing. The fatty acid in passively introduced phosphatidyl choline was released primarily as the intact phosphatide, whereas actively incorporated PC fatty acid was released primarily as free FA. As expected for an exchange process, the passively introduced PC was released at the same rate as it was introduced. However, the actively incorporated FA was released from the cell at a slower rate than its incorporation into PC. This latter phenomenon was explained by the observation of transfer of PC fatty acid to phosphatidyl ethanolamine and “neutral lipid” before its release to serum. This transfer process was inhibited by previous heating of the reincubation serum. The differences in the character of the released label, in the rate of release of the label, and in the influence of the reincubation serum all indicate separate pathways for the renewal of phosphatide introduced into red cells by these two routes.